Singing from the inside out exploring the voice, the singer and the song : a practical guide for the expressive singer - Doorn, Ineke van (ArtEZ Academia, 2016)
Singing from the inside out : exploring the voice, the singer and the song' is a practical guide to singing technique, practicing, performing and auditioning in pop, jazz, rock and hard rock, R & B, country, folk, musicals, reggae, ska, and other styles. This handbook is essential for both beginners and advanced singers. The many exercises, valuable tips and clear explanations it contains make it a useful tool for singing teachers as well